Transformasi Literasi Anak Usia Dini dengan E-Book: Pelatihan Book Creator untuk Guru Pendidikan Anak Usia Dini - Muhamamd Shodikul Haq; Dini Darmayanti; Ria Thalia; Rifda Alda Ufaira; Raidah Hanifah (Indonesian Institute For Counseling, Education and Therapy, 2024)
The development of digital literacy is essential for Early Childhood Education (PAUD) teachers to adapt to the rapid technological advances in education. This community service program focuses on enhancing the digital skills of PAUD teachers at TKTI Bustanul Ulum IV through training in Book Creator, a digital tool for creating interactive and engaging storybooks. The training aims to equip teachers with the ability to design and produce creative digital storybooks tailored to the developmental needs of children. By using Book Creator, teachers can integrate technology into their teaching practices, fostering an innovative and child-friendly learning environment. This program also supports the improvement of teaching materials, enabling teachers to create personalized resources that align with children’s interests and developmental stages. The initiative is expected to empower teachers at TKIT Bustanul Ulum IV, Bandar Jaya, Lampung to become more proficient in digital literacy, ultimately contributing to the cultivation of children’s interest in literacy and digital learning while promoting innovative teaching methods.